PHRASEOLOGY IN AIR TRAFFIC CONTROLLER’S COMMUNICATION - Khairunnisa Br. Batubara (EDUTECH, 2017)
The research design is qualitative research design. The instruments of data collection are voice recorder to record the data, camcorder to interview then observe the subject and a camera is used to capture some photographs to show the real situation in conducting as part of field research method. The findings of the study are drawn. (1) The types of phraseology used by ATC in this study are five; they are General Phraseology (GP), Radar Control Phraseology (RCP), Area Control Phraseology (Area CP), Approach Control Phraseology (App CP), and Aerodrome Control Phraseology (Aerodrome CP) as standard phraseology, and also Non – standard phraseology. (2) The patterns of phraseology used by ATC in communication with pilot are commonly systemized but sometimes it depends on the situation faced by controllers, there is no certain patterns used. (3) ATC commonly use standard phraseology which has been standardized by ICAO. ATC may combine the types of phraseology based on the condition and situation needed. In another case and situation, ATC sometimes used non – standard phraseology in communication with pilot, that’s why phraseology is the unique language used by ATC in their daily job, interact with pilots in a communication in order to prevent collisions, organize and expedite the flow of traffic, and provide information and other support for pilots.Key words: phraseology, air traffic controller, communication